Polyploidization of three Chrysanthemum varieties in vitro at various levels of colchicine soaking length - FERANITA HARING; MUH. FARID; IFAYANTI RIDWAN; MUHAMMAD FUAD ANSHORI; ANNASTYA NUR FADHILAH; KYLA BADZLIN HARTANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Haring F, Farid M, Ridwan I, Anshori MF, Fadhilah AN, Hartanto KB. 2024. Polyploidization of three Chrysanthemum varieties in vitro at various levels of colchicine soaking length. Biodiversitas 25: 3496-2503. The demand for new types and varieties of chrysanthemums with unique characteristics, such as various colors, shapes, and sizes, continues to increase. One approach that can be taken to achieve this diversity is through mutation techniques using chemical mutagens such as colchicine to obtain polyploid plants. This research, which aims to determine the best varieties and soaking time for colchicine in forming polyploid plants in vitro, has the potential to impact the field of Chrysanthemum breeding significantly. The research was arranged in a split-plot design (SPD), with the main plot being the Chrysanthemum variety (v), consisting of the Pinka Pinky (v1), Lollipop (v2), and Maruta (v3) varieties. The subplot is the soaking time at a colchicine concentration of 0.05%, which consists of 0 hours (t0), 4 hours (t1), 8 hours (t2), and 12 hours (t3). The parameters observed were the number of shoots, number of leaves, number of roots, time to sprout, time to root, time to form plantlets, and polyploidy analysis. Chromosome doubling in chrysanthemum plants after 0.05% colchicine induction with different soaking times produced mixoploid plants or the highest chromosome doubling of 9.18% + 18.82%, namely in the Lollipop variety with a soaking time of 12 hours. Meanwhile, other treatments did not show chromosome doubling and remained diploid but had different levels of chromosome variation.